STRUKTUR TEKS KARANGAN BAHASA JEPANG: ANALISIS PADA KARANGAN MAHASISWA ANGKATAN 2013 - Didik Nurhadi (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2017)
This article aimed to describe a essay of Unesa Student 2013 class, relating to the structure of  text and error analysis of Japanese language. These two viewpoints are considered important to see the student essay, with the reason that both of viewpoints relevant to the purpose of learning Japanese language 'sakubun' that is capable to communicate a case, circumstances, events, and opinions on to written language communication in good and right. The object  were taking from student essay results of Prodi Japanese Language and Education with total 22 students. The obtained data will be analyzed using interpretive methods to student essay of Unesa student 2013class, to describe the characteristics construction of essay text relating to the use of conjunctions and classification as well as text categorization based on the sentence or main paragraph placement.